CYTOTOXICITY ASSAY USING BRINE SHRIMP LETHALITY TEST ON COLLAGEN-CHITOSAN WOND DRESSING STERILIZED BY ULTRAVIOLET LIGHT - Ary Andini; Endah Prayekti; Devyana Dyah Wulandari; Ersalina Nidianti (Universitas Nahdlatul Ulama Surabaya, 2020)
Collagen gives a moist state on the wound area to accelerate the wound healing process. Chitosan is a polymer as known as non-toxic, antibacterial, antifungal, biodegradable, and biocompatible materials. Combination of collagen and chitosan expected to be the best biomaterials as a wound dressing for the healing process. The study aimed to determine cytotoxicity assay on collagen-chitosan wound dressing sterilized by ultraviolet (UV) Light using Brine Shrimp Lethality Test (BSLT) method. The test groups were divided into K0, K1, K2, and K3 groups. K0 contained pure chitosan as a control group, K1 contained collagen 25%-chitosan 75%, K2 contained collagen 50%-chitosan 50%, K3 contained collagen 75%-Chitosan 25%. Collagen extracted from skin and scalp of snakehead fish (Channa striata) then mixed with chitosan until formed collagen-chitosan wound dressing. This study used Brine Shrimp Level Test (BSLT) method with solution concentration 10, 50, 100, 250, 500, 750 and 1000 ppm. Based on the results showed that K0, K1, K2, and K3 group had LC50 >1000 that proven collagen-chitosan wound dressing was non-toxic materials. As conclusion of the study explained composite wound dressing based on collagen-chitosan in all groups that sterilized under UV-Light along 15 minutes was not toxic based on Brine Shrimp Lethality Test showed LC50 >1000.